CRISPR-Editing of Sweet Basil (Ocimum basilicum L.) Homoserine Kinase Gene for Improved Downy Mildew Disease Resistance - Zhang, Xiaoyu; Low, Yee Chen; Lawton, Michael A.; Simon, James E.; Di, Rong (Frontiers in Genome Editing, 2021)
Sweet basil (Ocimum basilicum L.) downy mildew disease (DM) caused by Peronospora belbahrii is a worldwide threat to the basil industry due to the lack of genetic resistance in sweet basil plants. In this study, we used CRISPR-gene editing to modify the sweet basil DM susceptibility gene homoserine kinase (ObHSK). Gene-edited plants that were challenged with P. belbahriiI displayed significantly reduced susceptibility to DM, based on phenotypic indices and on in vivo pathogen load. These results suggest that OsHSK plays a role in conditioning DM susceptibility, similar to that observed for the AtHSK gene in Arabidopsis. These results demonstrated that CRISPR-gene editing is a powerful tool to engineer sweet basil DM resistance and can be applied in sweet basil breeding.